Solve: $(3xy-2ay^2)dx+(x^2-2axy)dy=0$

The given differential equation is not exact.

The given differential equation is homogeneous.





With Integrating Factor of this form (ugly value), it is difficult to compute further integration, that is involved in solving the equation.

So, can we not solve the equation using the rule:

If in the differential eqn $Mdx+Ndy=0$, provided $ Mx+Ny \ne 0$, andM and N ar eboth homogeneous then


  • $\begingroup$ put $y=vx,$ ............. $\endgroup$ – Magneto Aug 8 '18 at 9:44

Hint: $$(3xy-2ay^2)dx+(x^2-2axy)dy=0$$ With $$M=3xy-2ay^2~~~~~~,~~~~~~N=x^2-2axy$$ then $$M_y=3x-4ay~~~~~~,~~~~~~N_x=2x-2ay$$ so the equation is not exact. For integrating factor $$\mu=\dfrac{M_y-N_x}{N}=\dfrac{x-2ay}{x(x-2ay)}=\dfrac1x$$ therefore $I=e^{\int \mu\ dx}=x$ is integrating factor.

Can you proceed?

  • $\begingroup$ Yes, I can proceed like this. But, can we not solve it using the homogeneous method? $\endgroup$ – Soumee Aug 8 '18 at 12:28
  • $\begingroup$ other answer is wity homogeneous method $\endgroup$ – Nosrati Aug 8 '18 at 12:51

Put y=vx

$\frac{dy}{dx} = \frac{2ay^2-3xy}{x^2-2axy} \\ v+x\frac{dv}{dx} = \frac{2av^2-3v}{1-2av}\\x\frac{dv}{dx} =\frac{4v(av-1)}{1-2av} \\ \frac{1-2av}{4v(av-1)}dv=\frac{dx}{x} \\(\frac{-1}{4v}-\frac{a}{4(av-1)})dv=\frac{dx}{x}\\v(av-1)x^4=C\\x^2y(ay-x)=C, \space some \space constant$

Other simpler way would be multiply with x

Given differential equation becomes:

$d(x^3 y)-ad(x^2y^2)=0$

U can directly integrate from here


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.